Rice (Oryza sativa) – potato (Solanum tuberosum) based cropping sequences in relation to production potential and economic returns under irrigated ecosystem of central plains - SINGH, RAJESH KUMAR; TIWARI, JAGESH KUMAR; SINGH, RAKESH KUMAR; SINGH, A K (The Indian Journal of Agricultural Sciences, 2017)
Rice (Oryza sativa L.) – wheat (Triticum aestivum L.) is the most important cropping system in India. It occupies 10.5 m ha productive lands in Indo-Gangetic plains and contributes about 25% of the national food production which accounts for 25% and 40% of the total area under rice and wheat, respectively. In some part of Indo-Gangetic plains, potato is being used as sandwich crop in rice-wheat cropping system by small and marginal farmers to increase the cropping intensity and net profits. Introduction of potato (Solanum tuberosum L.) into cropping system increasedthe productivity of the cropping system in many areas due to higher yield. To further increase the sustainability and profitability of the system, other high value crops can also be included in the system. Results showed that rice-potato-onion (534.08 q/ha), rice-potato-Japanese mint (501.46 q/ha), rice-potato-bitter gourd (484.38 q/ha) and rice-potato-bottle gourd (461.68 q/ha) crop sequences were statistically at par, however, produced significantly higher potato equivalent yield than rice-wheat (224.46 q/ha), rice-potato-wheat (325.50 q/ha) and rice-potatogreengram (399.75 q/ha) crop sequences. The present study indicated that the rice-potato-Japanese mint and ricepotato-onion crop sequences were more productive and economically viable as they fetched more net returns and can be a better option for the farmers of the Central Plains zone of India, and the same cropping sequences were also adjudged as most sustainable by the farmers in their agricultural production system.